Management of Immature Open Apex with MTA and PRF Placement - Pradnya Vilas Bansode (New Advances in Medicine and Medical Science Vol. 1, 2023)
The major challenges associated with the endodontic treatment of teeth with open apices are achieving adequate access to the wide canal, complete debridement, canal disinfection, and optimal sealing of the root canal system. In the absence of a natural apical constriction, it is imperative to create an apical barrier and allow three-dimensional adaptation of obturating material within the root canal system [4]. Injuries to the dental pulp in immature teeth stop root development, leading to several issues. The management of nonvital open-apex teeth can be done in several ways. Platelet-rich fibrin (PRF) is widely used to accelerate soft and hard tissue healing which can be used as a matrix. A 21-year-old male reported the chief complaint of a broken, discolored tooth, occasional pain, swelling, and pus discharge in the upper front region. The diagnosis of chronic periapical abscess with open apex and 11 was determined in light of the clinical and radiologic features. Triple antibiotic paste was applied to the canal at the initial appointment. The mineral trioxide aggregate (MTA) plug was placed across the periapical region of the body during the second visit after 21 days. The tooth was asymptomatic and non-tender at the follow-up appointment after six months.